Heat transfer enhancement using two isothermal blocks in a cylindrical heat exchanger - Touzani S. (MATEC Web of Conferences, 2019)
The influence of two isothermal blocks placed in a low position φm=0.18π in a cylindrical heat exchanger is numerically studied. The governing equations are discretized by the centered finite difference method using the ADI scheme. By varying Rayleigh number range between 1000 and 10000, we are interested in the local Nusselt number and the local efficiency variations as a function of the angular coordinate φ. In one hand, we found that heat transfer is important in the superior zone of the annulus for high Ra and in the central zone for low Ra. On the other hand, compared to the without blocks configuration, heat transfer in the inferior and central zones is improved for all Ra.